2022
DOI: 10.3390/polym14235246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Accelerated Aging on the Properties of Parylene C

Abstract: The polymer Parylene combines a variety of excellent properties and, hence, is an object of intensive research for packaging applications, such as the direct encapsulation of medical implants. Moreover, in the past years, an increasing interest for establishing new applications for Parylene is observed. These include the usage of Parylene as a flexible substrate, a dielectric, or a material for MEMS, e.g., a bonding adhesive. The increasing importance of Parylene raises questions regarding the long-term reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Due to constructive and destructive interferences caused by the measurement setup in transmission mode, the obtained spectra featured a superposition with a sinus curve. In order to remove this sinus and smooth the spectra, the data were mathematically processed as described in 21 in detail. Briefly it can be summarized by fitting the sinus according to Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Due to constructive and destructive interferences caused by the measurement setup in transmission mode, the obtained spectra featured a superposition with a sinus curve. In order to remove this sinus and smooth the spectra, the data were mathematically processed as described in 21 in detail. Briefly it can be summarized by fitting the sinus according to Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the fact that the Parylene coating and sacrificial layer release are the last process steps in the presented technology flow, particularly, fabrication and integration processes with an increased thermal budget are avoided. Hence, the alteration of the Parylene properties is prevented as well [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2] However, other studies have revealed a dependency of the Young's modulus and the hardness on the thermal budget, which is assumed to be caused by recrystallization of the partially crystalline polymer. [5] Hence, free-standing Parylene C membranes of 5 µm thickness were fabricated according to the process and using the equipement given in the literature [2] and stored under the typical conditions of a bonding process, i.e. 30 min in vacuum at 260 °C, 280 °C, 300 °C, and 320 °C, respectively.…”
Section: A Impact Of the Bonding Conditions On Parylene Cmentioning
confidence: 99%